2020
DOI: 10.3390/cancers12102974
|View full text |Cite
|
Sign up to set email alerts
|

From Tumor Mutational Burden to Blood T Cell Receptor: Looking for the Best Predictive Biomarker in Lung Cancer Treated with Immunotherapy

Abstract: Despite therapeutic advances, lung cancer (LC) is one of the leading causes of cancer morbidity and mortality worldwide. Recently, the treatment of advanced LC has experienced important changes in survival benefit due to immune checkpoint inhibitors (ICIs). However, overall response rates (ORR) remain low in unselected patients and a large proportion of patients undergo disease progression in the first weeks of treatment. Therefore, there is a need of biomarkers to identify patients who will benefit from ICIs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…44,47 Although PD-L1 expression level is widely used as an immune biomarker, it is not an ideal biomarker because some patients with low PD-L1 expression levels respond to immunotherapy and others with high levels do not respond to immunotherapy. 48,49 PD-L1 expression levels are useful for deciding whether to use single-agent immunotherapy or combination immunotherapy.…”
Section: Immune Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations
“…44,47 Although PD-L1 expression level is widely used as an immune biomarker, it is not an ideal biomarker because some patients with low PD-L1 expression levels respond to immunotherapy and others with high levels do not respond to immunotherapy. 48,49 PD-L1 expression levels are useful for deciding whether to use single-agent immunotherapy or combination immunotherapy.…”
Section: Immune Biomarkersmentioning
confidence: 99%
“…50 Theoretically, high TMB levels will correlate with high neoantigen levels that will activate an antitumor immune response. 48 TMB levels are typically high in patients with NSCLC who are smokers or former smokers. Low TMB is more commonly detected in never-smokers.…”
Section: Immune Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were observed by Wang et al [ 39 ]. Another clinical trial (B-F1RST, NCT02848651, n = 152) also showed a correlation between a high bTMB and atezolizumab response in NSCLC patients, using the same cut-off for bTMB as in the POPLAR and OAK studies [ 41 ].…”
Section: Cell-free Dnamentioning
confidence: 99%